2019
DOI: 10.1055/a-0881-2905
|View full text |Cite
|
Sign up to set email alerts
|

Total and Regional Body Composition of NCAA Division I Collegiate Baseball Athletes

Abstract: This study’s purpose was to evaluate total, regional, and throwing versus non-throwing arm body composition measurements between various positions of NCAA Division I male baseball players using dual X-ray absorptiometry (DXA). Two hundred and one collegiate baseball athletes were measured using DXA. Visceral adipose tissue (VAT), total and regional fat mass (FM), lean mass (LM), and bone mineral density (BMD) were measured. Athletes were separated into: pitchers (n=92), catchers (n=25), outfielders (n=43), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
3
14
3
Order By: Relevance
“…These results would seem to agree with the current study wherein the throwing arm had significantly higher lean mass, BMC, and BMD compared to the non-throwing arm for all positions. Importantly, the current study's results are similar to those of a previous study [3] in male baseball players in which the throwing arm was observed to have more lean mass, BMC, and BMD than the non-throwing arm for nearly all positions.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results would seem to agree with the current study wherein the throwing arm had significantly higher lean mass, BMC, and BMD compared to the non-throwing arm for all positions. Importantly, the current study's results are similar to those of a previous study [3] in male baseball players in which the throwing arm was observed to have more lean mass, BMC, and BMD than the non-throwing arm for nearly all positions.…”
Section: Discussionsupporting
confidence: 88%
“…The most important study observations included: (a) there were no significant total or regional lean mass or BMD differences among the positions; (b) there were significant total and regional body fat mass differences between pitchers and outfielders; (c) there were significant throwing versus non-throwing arm differences within each position; and (d) there were no significant VAT mass differences across positions despite differences in total and regional composition by position. Notably, unlike a previous study of body composition in Division I baseball players [3], a softball players' position has very little effect upon the athletes' total and regional body composition (the only differences are that pitchers are taller and have more fat mass than outfielders). However, similar to a previous study [3], the sports' demands contribute to the throwing arm having greater total mass, fat mass, lean mass, BMD, and BMC than the non-throwing arm in most positions.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Importantly, previous studies have not (a) measured basketball athletes' regional body composition using DXA or (b) compared total and regional composition across all five basketball player positions. Furthermore, only five known studies have examined VAT mass in any athlete population [13][14][15][16][17]. Quantifying VAT mass is important, as it is associated with cardiometabolic risk and thus indicative of an individual's health [17][18][19][20].…”
Section: Total and Regional Body Composition Of Ncaa Division I Collementioning
confidence: 99%